Cochrane Database of Systematic Reviews 2008
DOI: 10.1002/14651858.cd004576.pub2
|View full text |Cite|
|
Sign up to set email alerts
|

Interventions for treating wrist fractures in children

Abstract: Limited evidence supports the use of removable splintage for buckle fractures and challenges the traditional use of above-elbow casts after reduction of displaced fractures. Although percutaneous wire fixation prevents redisplacement, the effects on longer term outcomes including function are not established. Further research is warranted on the optimum approach, including splintage, for buckle fractures; and on the use of below-elbow casts and indications for surgery for displaced wrist fractures in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(15 citation statements)
references
References 22 publications
0
11
0
4
Order By: Relevance
“…Eine sekundäre Dislokation entsteht nie, sofern keine Biegungskomponente vorliegt. Die Behandlung besteht in der Gipsruhigstellung für 2 bis 3 Wochen [1]. Sobald eine Biegungskomponente als Ursache hinzukommt und die aufzunehmende Energie die Elastizität des Knochens übersteigt, kommt es zu Dislokationen.…”
Section: Wulstfrakturenunclassified
See 2 more Smart Citations
“…Eine sekundäre Dislokation entsteht nie, sofern keine Biegungskomponente vorliegt. Die Behandlung besteht in der Gipsruhigstellung für 2 bis 3 Wochen [1]. Sobald eine Biegungskomponente als Ursache hinzukommt und die aufzunehmende Energie die Elastizität des Knochens übersteigt, kommt es zu Dislokationen.…”
Section: Wulstfrakturenunclassified
“…Um eine sekundäre Dislokation sicher vermeiden zu können, wird von vielen Autoren eine primäre Reposition mit perkutaner K-Draht-Osteosynthese gefordert [11,12,18]. Obwohl diese die sekundäre Dislokation weitgehend verhindert, gibt es keine belastbaren Daten zu den Langzeitergebnissen, die in einem Cochrane-Review dringend gefordert werden [1,13].…”
Section: Grünholzfrakturen Und Komplette Frakturen Mit Angulationunclassified
See 1 more Smart Citation
“…Radiographs fractures are inherently stable and the risk of displacement is very low or non-existent [3][4][5][6][7] . In a review of nine studies on torus fractures [3,[6][7][8][9][10][11][12][13] , May and Grayson (2009) found that in none of the studies was there loss of position, lack of recovery, need for orthopaedic intervention or ongoing pain. The authors concluded that buckle fractures will heal regardless of the treatment the patient receives [14] .…”
Section: Introductionmentioning
confidence: 99%
“…These factors make it difficult to evaluate the reliability of the evidence presented and the review's conclusions should be interpreted with caution [19] . In the current literature, one systematic review was found that compared splint and cast in torus factures among other types of interventions in different wrist fractures in children [8] . It concluded that the limited evidence supports the use of removable splint…”
Section: Introductionmentioning
confidence: 99%